RELATIONSHIP BETWEEN PHYSICAL ACTIVITY, JOGGING REGULARLY, AND THE DEGREE OF DYSMENORRHEA IN STUDENTS OF THE NURSING DEPARTMENT, MADURA STATE POLYTECHNIC - Nugrahani, Cantika Iva; Iszakiyah, Nur; Kuzzairi, Kuzzairi; Ervina, Ervina (Media Ilmiah Kesehatan Indonesia, 2025)
Dysmenorrhea is a condition of pain and cramps experienced by women before they experience menstruation or when menstruation occurs. Physical activity can be done in the form of sports such as jogging. This study aimed to determine the relationship between physical activity, jogging, and the degree of dysmenorrhea in 3rd year female students majoring in Nursing at the Madura State Polytechnic. This study used an analytical correlation method using the Analytic Correctional-Cross Sectional. The population was 25 people, and the sample in this study was 3rd-year female students majoring in Nursing at the Madura State Polytechnic who experienced dysmenorrhea and did physical jogging activities routinely and regularly. Data collection by providing a closed-ended questionnaire for physical jogging activities and a Numeric Rating Scale (NRS) questionnaire for the degree of dysmenorrhea, and analysis using the Spearman Rank test statistical analysis method with α = <0.05. The results obtained a significant value of 0.006, meaning <0.05 means that physical jogging activities are related to the degree of dysmenorrhea, where most female students who experience mild dysmenorrhea do physical jogging activities routinely. The limitations of this study are the relatively small number of samples taken and other factors that can affect the degree of dysmenorrhea, such as stress levels, nutritional status, lifestyle, and family history. Based on the results of the research that has been conducted, it can be concluded that the degree of dysmenorrhea can be reduced if someone routinely does physical activity, in this case by jogging.